Impact-resistant high-thermal-conductivity regenerated PET composite material and preparation method thereof
By carbonizing agent and sawdust carbonization to form porous carbon materials, and recrystallization and micro-foaming are used to use carbon oxide fillers and modified chain extenders to perform recrystallization and micro-foaming, the problem of insufficient impact resistance and thermal conductivity of regenerated PET composite polyester materials is solved, and the problem of insufficient impact resistance and thermal conductivity of regenerated PET composite polyester materials is achieved. Efficient performance improvement.
Patent Information
- Application Number
- CN202411809936.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The impact resistance and thermal conductivity of existing recycled PET composite polyester materials are insufficient, especially when sheet-like structure fillers are prone to local stress concentration and slippage under the action of force, reducing the overall structural stability of the material.
Carbonization agent and sawdust carbonization form porous carbon materials, and recrystallization and micro-foaming are carried out through the use of carbon oxide fillers and modified chain extenders to form a uniform and fine bubble structure to promote the foaming of the carbon layer and Flame retardant gas release, enhancing the impact, heat conductivity and wear resistance of the material.
The impact, heat and wear resistance of regenerated composite polyester is significantly improved, forming a flame-retardant regenerated composite polyester material that is impact-resistant, highly thermally conductive and flame-resistant.
Smart Images

Figure CN119286041A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycled polyester processing, and in particular to an impact-resistant and highly thermally conductive recycled PET composite material and a preparation method thereof. Background Art
[0002] Recycled polyester materials have important value in terms of environmental friendliness and resource recycling, but their inherent molecular chain degradation, crystallinity changes and other factors lead to relatively poor impact resistance and thermal conductivity, limiting their promotion in high-performance applications. In order to improve the impact resistance and thermal conductivity of recycled polyester materials, toughening agents, nanofillers or blending modifications are often added to enhance the flexibility of the molecular chain and the effectiveness of the heat conduction path, forming a heat conduction network in the recycled polyester matrix, thereby effectively improving its thermal conductivity. At the same time, the use of toughening agents can reduce the expansion of microcracks during impact and improve the impact resistance of the material.
[0003] Prior art CN117164828A discloses a high-strength recycled PET plastic particle, which is prepared by adding PET bottle flakes, a depolymerizing agent and ethylene glycol sodium titanate into a reactor, introducing nitrogen and heating the reactor to 195-205° C. in an oil bath, stirring and condensing the reactor to react, to obtain an alcoholysis product, adding triphenyl phosphate and a monolayer molybdenum disulfide microflake to the alcoholysis product, stirring and mixing, and then vacuuming and reducing the pressure to -0.02MPa, first heating the reactor to 200-210° C. and keeping the temperature for 2h, introducing nitrogen and keeping the temperature at 30-50Pa, and then heating the reactor to 27-280° C., and carrying out a polycondensation reaction for 2h under stirring, extruding the recycled PET melt from the bottom valve of the reactor, cold water solidifying the pelletized pellets, and drying the pellets to a constant weight to obtain high-strength recycled PET plastic particles, wherein the obtained plastic particles have higher strength and more excellent thermal stability.
[0004] However, the above patent content is to introduce a single layer of molybdenum disulfide microsheets in the process of polyester depolymerization and re-condensation to enhance the strength of recycled polyester particles. However, due to the layered distribution of the sheet-like structure filler, the force transmission is mainly concentrated in the plane direction, and it is impossible to evenly disperse the force to the entire space like a three-dimensional structure filler. Under the action of external force, local stress concentration will appear inside the material, increasing the risk of deformation or damage of the material. In addition, when the sheet-like filler is subjected to force, relative slip or stratification may occur, which reduces the overall structural stability of the material. Therefore, the impact resistance of the recycled polyester material obtained by the above technology needs to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an impact-resistant and highly thermally conductive recycled PET composite material and a preparation method thereof, so as to solve the technical problem in the prior art that the thermal conductivity and impact resistance of recycled composite polyester need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing an impact-resistant and highly thermally conductive recycled PET composite material, comprising the following steps:
[0008] S1, adding recycled polyester and a carbonization promoter into a twin-screw extruder for melt extrusion to obtain a green body, and subjecting the green body to solid phase polycondensation to obtain a hybrid polyester;
[0009] S2, mixing the hybrid polyester and sawdust to obtain a mixed powder by grinding and sieving, and carbonizing the mixed powder to obtain a porous carbon material;
[0010] S3, adding the recycled polyester and the modified chain extender into a twin-screw extruder for melt extrusion to obtain a substrate, and repeating the solid phase polycondensation step in step S1 to obtain a cross-linked polyester;
[0011] S4, melt-blending the cross-linked polyester, the oxidized carbon filler and the auxiliary materials to obtain a recycled composite polyester body;
[0012] S5. Recrystallize and micro-foam the recycled composite polyester blank with carbon dioxide to obtain the recycled composite polyester.
[0013] Furthermore, in step S1, the ratio of the recycled polyester to the carbonizing agent is 8-10 g:2-3 g; and the preparation method of the carbonizing agent comprises the following steps:
[0014] A1. Add N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, trans,trans-1,3-butadiene-1,4-dicarboxylic acid and p-toluenesulfonic acid into a vacuum reactor, increase the temperature of the reactor to 240-260° C., and carry out vacuum insulation reaction for 6-8 hours to obtain a carbonization promoter precursor;
[0015] The reaction equation for preparing the carbonization agent precursor is:
[0016] Where: , “*” represents the terminal active site.
[0017] The reaction principle for preparing the carbonizer precursor is as follows: under the promotion of high temperature and catalyst, N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine and trans,trans-1,3-butadiene-1,4-dicarboxylic acid undergo solid phase condensation, and the chain growth continues through polycondensation to finally prepare the carbonizer precursor.
[0018] A2. Add 30-40wt% peracetic acid solution and dichloromethane into the reactor and stir. Lower the temperature of the reactor to -10-0°C, keep warm and stir for 5-10 minutes, add the carbonizer precursor into the reactor, and use phosphate buffer to adjust the pH of the system to 5-7, keep warm and stir for 0.5-2 hours, and post-treat to obtain the carbonizer.
[0019] The reaction equation for preparing the carbonization promoter is: The reaction principle for preparing the carbonizing agent is as follows: under the oxidation of peroxy acid, the carbon-carbon double bond in the carbonizing agent precursor is oxidized into an epoxy group, and the carbonizing agent is finally prepared.
[0020] Furthermore, in step A1, the amount ratio of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, trans, trans-1,3-butadiene-1,4-dicarboxylic acid and p-toluenesulfonic acid is 8-10g:2-3g:0.3-0.5g; in step A2, the amount ratio of 30-40wt% peracetic acid solution, dichloromethane and carbonization promoter precursor is 3-5mL:30-40mL:10-12g, and the post-treatment includes: after the reaction is completed, the reaction kettle is heated to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the carbonization promoter is obtained by reduced pressure distillation until no liquid is extracted.
[0021] Furthermore, in step S1, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, and 280°C, respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar to obtain the billet by melt extrusion.
[0022] Furthermore, in step S1, the solid phase polycondensation operation is:
[0023] B1. Add the green body into a reactor, heat the reactor to 80-90°C at a heating rate of 1-2°C / min, keep the temperature for 1 hour, then heat the reactor to 110-120°C at a heating rate of 1-2°C / min, keep the temperature for 3 hours, turn the material every 1 hour, and naturally cool after heating to obtain a pre-crystallized green body;
[0024] B2. Transfer the pre-crystallized body to a vacuum drum, set the drum temperature to 200-225°C, the vacuum degree to 40-50Pa, the rotation speed to 15-20rpm, and keep the drum warm for 2-3h to obtain a hybrid polyester.
[0025] The reaction principle for preparing hybrid polyester is as follows: in the early stage of the reaction, the crystal state of the polyester blank is controlled by slowly heating and keeping warm steps, so that its molecular chains gradually move at a lower temperature, so as to form an ordered crystal region and obtain a pre-crystallized blank; further, the oxygen content in the reaction is reduced in a vacuum environment, thereby reducing oxidative degradation, the rotation of the drum ensures that the blank is heated evenly, the high temperature causes the polyester molecular chains to further move and rearrange, the polyester chain segments break to generate free radicals that react with epoxy groups on the surface of the carbonizing agent, and the hybrid polyester is prepared.
[0026] Furthermore, in step S2, the usage ratio of hybrid polyester to sawdust is 1-2g:1g, the mesh size of the sieve is 300-600 mesh, and the carbonization operation is as follows: the mixed powder is placed in a tubular furnace, nitrogen is introduced for protection, the tubular furnace is heated to 70-80°C at a heating rate of 5-8°C / min, and the temperature is kept warm for 20-30min, and the tubular furnace is continued to be heated to 800-850°C at a heating rate of 5-8°C / min. After keeping warm for 2-4h, the heating is stopped, nitrogen is kept introduced, and the tubular furnace is naturally cooled to room temperature to obtain a porous carbon material.
[0027] The principle of preparing porous carbon materials is as follows: during the carbonization process, the phosphoric acid groups in the carbonizing agent decompose to produce acidic substances to promote the carbonization of melamine segments, polyester segments and sawdust. The decomposition of melamine segments produces gases that promote the generation of micropores and mesopores in the carbon material, and finally a porous carbon material is prepared.
[0028] Further, the modification operation of the porous carbon material includes the following steps:
[0029] C1. Grinding and sieving the porous carbon material to obtain a micron carbon filler;
[0030] C2, adding 98.0wt% concentrated sulfuric acid to the reactor and stirring, adding sodium nitrate during stirring, and after lowering the temperature of the reactor to 0-5°C, adding potassium permanganate to the reactor, stirring for 5-10 minutes, and then adding micron carbon filler, raising the temperature of the reactor to 35-40°C, and keeping the temperature for reaction for 4-6 hours, and post-treating to obtain oxidized carbon filler;
[0031] The reaction principle for preparing oxidized carbon fillers is as follows: under the promotion of 98.0wt% concentrated sulfuric acid and sodium nitrate, the oxidation performance of potassium permanganate is significantly enhanced, and the micron carbon fillers are continuously oxidized during the heating process. After the oxidation is completed, the reaction liquid is neutralized with hydrogen peroxide solution, and finally the oxidized carbon fillers are obtained through a series of operations such as filtration.
[0032] C3. Add carbon oxide filler, carbonization promoter, triethylamine and dichloromethane into a reactor and stir. The temperature of the reactor is raised to 30-50° C. and stirred for 1-2 hours. Post-process to obtain a modified chain extender.
[0033] The reaction principle for preparing the modified chain extender is as follows: after oxidation, active groups such as hydroxyl, carboxyl and epoxy groups are formed on the surface of the micron carbon filler. These active functional groups such as hydroxyl react with active groups such as epoxy groups on the surface of the carbonization promoter to form crosslinks on the surface of the oxidized carbon filler, and finally a modified chain extender is prepared.
[0034] Further, in step C1, the mesh size of the sieve is 2000-3000 mesh; in step C2, the stirring rate of the reactor is 80-120 rpm, and the amount ratio of 98.0wt% concentrated sulfuric acid, sodium nitrate, potassium permanganate and micron carbon filler is 200-210mL:3-5g:30-40g:10-15g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, 30wt% hydrogen peroxide solution is added dropwise to the reactor until the reaction liquid turns yellow, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed with deionized water and ethanol for 3 -5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized carbon filler; in step C3, the amount ratio of the oxidized carbon filler, the carbonization promoter, triethylamine and dichloromethane is 8-10g:3-5g:0.8-1.2g:40-60mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and after washing with deionized water and ethanol for 3-5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a modified chain extender.
[0035] Furthermore, in step S3, the ratio of the amount of the recycled polyester to the modified chain extender is 8-10 g:3-5 g.
[0036] Furthermore, in step S3, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, and 280°C, respectively, and the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar to obtain the substrate by melt extrusion.
[0037] Furthermore, in step S3, the solid phase polycondensation operation is as follows: the substrate is added to the reactor, the reactor is heated to 80-90°C at a heating rate of 1-2°C / min, and the temperature is kept for 1 hour, and then the temperature is increased to 110-120°C at a heating rate of 1-2°C / min, and the temperature is kept for 3 hours, and the material is turned over every 1 hour. After the heating is completed, the pre-crystallized substrate is obtained after natural cooling, and the pre-crystallized substrate is transferred to a vacuum drum, the drum temperature is set to 200-225°C, the vacuum degree is set to 40-50Pa, the rotation speed is 15-20rpm, and the heat treatment is carried out for 2-3 hours to obtain a cross-linked polyester.
[0038] Furthermore, in step S4, the auxiliary materials include: antioxidant, plasticizer, antistatic agent and stabilizer, and the amount ratio of cross-linked polyester, oxidized carbon filler, antioxidant, plasticizer, antistatic agent and stabilizer is 80-100g:10-12g:6-8g:10-15g:3-5g:4-6g.
[0039] Furthermore, the antioxidant is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl)phosphate and hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate; the plasticizer is one or more of dioctyl phthalate, dibutyl phthalate and dioctyl adipate; the antistatic agent is one or more of ethoxylated alkylamine, distearyl dimethyl ammonium chloride and polyoxyethylene ether; the stabilizer is one or more of 2-hydroxy-4-n-octyloxybenzophenone, bis(2,2,6,6-tetramethylpiperidinyl)methylene succinate and 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole.
[0040] Furthermore, in step S4, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, and 280°C, respectively, the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar to obtain the recycled composite polyester blank through melt extrusion.
[0041] Furthermore, in step S5, the carbon dioxide recrystallization and micro-foaming operations are as follows: placing the regenerated composite polyester body in a high-pressure reactor, placing the high-pressure reactor in a salt bath furnace, exhausting the air in the high-pressure reactor with carbon dioxide gas, and then introducing 15-18MPa carbon dioxide gas into the high-pressure reactor using a booster device, adjusting the temperature of the salt bath furnace to 25-30°C, and after heat preservation for 2-4h, the temperature of the salt bath furnace rises to 60-80°C, observing the internal pressure of the high-pressure reactor during the heating process, using valves on both sides to vent and release pressure, controlling the pressure in the reactor to be less than 30MPa, and heat-retaining for 1-2h, and rapidly releasing the pressure to obtain the regenerated composite polyester.
[0042] The reaction principle for preparing recycled composite polyester is as follows: under high pressure and low temperature environment, carbon dioxide molecules can enter the molecular structure of polyester materials, causing a certain degree of swelling. The penetration of carbon dioxide molecules makes the polyester molecular chains soft and easy to move, providing the necessary environment for crystallization. The polyester molecular chains gradually move and rearrange under the swelling effect of carbon dioxide, thereby forming a more ordered crystal region and recrystallization. When the temperature is raised to 60-80°C, the molecular motion of the polyester material is enhanced, and the solubility of carbon dioxide under high pressure and increased temperature decreases, making it easier for carbon dioxide to precipitate. The rapid pressure release process at this time will cause carbon dioxide to diffuse rapidly from the polyester matrix, generating tiny bubbles, resulting in the formation of a microporous structure inside the polyester material, and finally preparing recycled composite polyester.
[0043] The invention also provides an impact-resistant and high-thermal-conductive recycled PET composite material, which is obtained by adopting a preparation method of the impact-resistant and high-thermal-conductive recycled PET composite material.
[0044] The present invention has the following beneficial effects:
[0045] 1. In the process of preparing the recycled composite polyester, the present invention prepares a carbonizing agent to promote the formation of porous carbon materials during the carbonization of the recycled polyester and sawdust, thereby expanding the utilization options of the recycled polyester. The carbonizing agent self-assembles on the surface of the oxidized carbon filler to obtain a modified chain extender. While the modified chain extender hybridizes the organic chain segments, it acts as a nucleation site to promote the recrystallization of the recycled composite polyester blank during the recrystallization and micro-foaming process, promotes the diffusion of the fluid, and forms a uniform and fine bubble structure. During the combustion process, the carbonizing agent decomposes to form a molten carbon layer, and releases flame-retardant gas to promote the foaming of the carbon layer, which cooperates with the carbon skeleton to prevent the spread of flames, and finally obtains an impact-resistant, heat-conductive and wear-resistant flame-retardant recycled composite polyester.
[0046] 2. The present invention firstly selects and prepares a carbonization promoter, which has a large number of epoxy groups inside. During the solid phase polycondensation process, the chain segments of the hybridized regenerated polyester have a complex spatial structure to obtain a hybrid polyester. The hybrid polyester forms a stable carbon skeleton during the carbonization process, which reduces the volatilization loss of organic matter during the pyrolysis process, and forms abundant pores to generate microporous and mesoporous carbon materials. The phosphoric acid structure inside the chain segments decomposes during the carbonization process to produce acidic substances, which further promote the carbonization of the mixed powder obtained by mixing the hybrid polyester and sawdust. The melamine component in the carbonization promoter releases a large amount of gas during the carbonization process, which further promotes the formation of micropores and mesopores to obtain a porous carbon material.
[0047] 3. After the porous carbon material is crushed and oxidized, the carbonizing agent acts as a cross-linking chain segment and self-assembles on the surface of the oxidized carbon filler to obtain a modified chain extender. The regenerated polyester uses the modified chain extender as a skeleton to hybridize the spatial structure of the regenerated polyester on its surface, and the oxidized carbon filler that has not undergone surface self-assembly is used as a filler to participate in the preparation of the regenerated composite polyester embryo. The oxidized carbon filler has a large number of active functional groups on its surface after oxidation, and has excellent compatibility with organic materials. The rich carbon skeleton structure in the regenerated composite polyester embryo not only improves the thermal conductivity of the final product, the regenerated composite polyester, but also promotes the recrystallization of the regenerated composite polyester embryo as a nucleation site, and promotes the diffusion of the supercritical fluid. In the process of depressurization, it acts as a bubble nucleus to help form a more uniform and fine bubble structure. In the process of combustion, the phosphoric acid group in the carbonizing agent self-assembled on the surface of the modified chain extender decomposes to promote the carbonization of the melamine chain segment to form a molten carbon layer, and releases flame-retardant gas to promote the foaming of the carbon layer, which cooperates with the carbon skeleton to prevent the spread of flames, and finally prepares an impact-resistant, heat-conductive and wear-resistant flame-retardant regenerated composite polyester. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0049] Figure 1 This is a SEM image of the porous carbon material prepared in Example 3 of the present invention;
[0050] Figure 2 for Figure 1 Magnified image of . DETAILED DESCRIPTION
[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] This embodiment provides a method for preparing an impact-resistant and highly thermally conductive recycled PET composite material, comprising the following steps:
[0054] Step 1: Preparation of porous carbon materials
[0055] Weigh: 18.0 g of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 6.0 g of trans, trans-1,3-butadiene-1,4-dicarboxylic acid and 0.8 g of p-toluenesulfonic acid are added into a vacuum reactor, the temperature of the reactor is raised to 240° C., and the reaction is carried out under vacuum insulation for 6 hours to obtain a carbonization promoter precursor;
[0056] Weigh: 8.0mL 30.0wt% peracetic acid solution and 72.0mL dichloromethane are added to the reactor and stirred. The temperature of the reactor is lowered to 0°C, and the mixture is stirred for 5 minutes. 24.0g of carbonization promoter precursor is added to the reactor, and the pH of the system is adjusted to 7 with phosphate buffer, and the mixture is stirred for 1 hour. After the reaction is completed, the reactor is heated to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and the reaction mixture is distilled under reduced pressure until no liquid is extracted to obtain a carbonization promoter;
[0057] Weigh: 18.0 g of recycled polyester and 5.0 g of a carbonizing agent are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260° C., 260° C., 265° C., 265° C., 270° C., 270° C., 280° C., and 280° C., the main engine speed of the twin-screw extruder is 80 rpm, and the pressure is 100 bar to obtain a green body through melt extrusion;
[0058] The green body was added into the reactor, and the temperature of the reactor was raised to 80°C at a heating rate of 1°C / min, and kept at that temperature for 1 hour, and then raised to 110°C at a heating rate of 1°C / min, and kept at that temperature for 3 hours, and the material was turned over every 1 hour. After the heating was completed, the green body was naturally cooled to obtain a pre-crystallized green body;
[0059] The pre-crystallized body was transferred to a vacuum drum, the drum temperature was set to 200°C, the vacuum degree was set to 40Pa, the rotation speed was 15rpm, and the heat preservation treatment was performed for 2h to obtain a hybrid polyester;
[0060] Weigh: 20.0g of hybrid polyester and 15.0g of sawdust are mixed and ground, and then passed through a 400-mesh sieve to obtain a mixed powder. The mixed powder is placed in a tubular furnace, and nitrogen is introduced for protection. The tubular furnace is heated to 70°C at a heating rate of 5°C / min, and the temperature is kept warm for 20min. The tubular furnace is further heated to 800°C at a heating rate of 5°C / min. After keeping warm for 2h, the heating is stopped, and nitrogen is kept introduced. The tubular furnace is naturally cooled to room temperature to obtain a porous carbon material.
[0061] Step 2: Preparation of cross-linked polyester
[0062] The porous carbon material is ground and passed through a 2000-mesh sieve to obtain a micron carbon filler;
[0063] Weigh: 200.0mL 98.0wt% concentrated sulfuric acid is added to the reactor and stirred. During the stirring process, 4.0g sodium nitrate is added, and after the temperature of the reactor is lowered to 0°C, 30.0g potassium permanganate is added to the reactor. After being kept warm and stirred for 8min, 12.0g micron carbon filler is added. The temperature of the reactor is raised to 35°C, and the reaction is kept warm for 4h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and 30wt% hydrogen peroxide solution is added dropwise to the reactor until the reaction liquid turns yellow. The reaction liquid is filtered to collect the filter cake, and after washing with deionized water and ethanol for 3 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized carbon filler;
[0064] Weigh: 18.0g of carbon oxide filler, 8.0g of carbonization promoter, 1.8g of triethylamine and 80.0mL of dichloromethane, add them into the reactor and stir, raise the temperature of the reactor to 30°C, keep warm and stir for 1h, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with deionized water and ethanol for 3 times, transfer the filter cake to a drying oven at 60°C and vacuum dry it until the filter cake has a constant weight, to obtain a modified chain extender;
[0065] Weigh: 80.0 g of recycled polyester and 36.0 g of modified chain extender are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260° C., 260° C., 265° C., 265° C., 270° C., 270° C., 280° C., and 280° C., the main engine speed of the twin-screw extruder is 80 rpm, and the pressure is 100 bar to obtain a substrate through melt extrusion;
[0066] The substrate was added into the reactor, and the temperature of the reactor was increased to 80°C at a heating rate of 2°C / min. After being kept warm for 1 hour, the temperature was increased to 110°C at a heating rate of 1°C / min, and kept warm for 3 hours. The material was turned over every 1 hour. After the heating was completed, the substrate was naturally cooled to obtain a pre-crystallized substrate. The pre-crystallized substrate was transferred to a vacuum drum, the drum temperature was set to 210°C, the vacuum degree was set to 40Pa, the rotation speed was 15rpm, and the heat treatment was performed for 2 hours to obtain a cross-linked polyester.
[0067] Step 3: Preparation of recycled composite polyester
[0068] Weigh: 84.0g of cross-linked polyester, 10.8g of carbon oxide filler, 6.4g of tri(2,4-di-tert-butylphenyl) phosphate, 12.0g of dibutyl phthalate, 4.8g of ethoxylated alkylamine and 5.6g of 2-hydroxy-4-n-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, 280°C, the main engine speed of the twin-screw extruder is 80rpm, the pressure is 125bar, and a recycled composite polyester blank is obtained by melt extrusion;
[0069] The recycled composite polyester blank is placed in a high-pressure reactor, and the high-pressure reactor is placed in a salt bath furnace. After exhausting the air in the high-pressure reactor with carbon dioxide gas, 15MPa carbon dioxide gas is introduced into the high-pressure reactor using a booster device. The temperature of the salt bath furnace is adjusted to 25°C. After insulation treatment for 2 hours, the temperature of the salt bath furnace is raised to 60°C. During the heating process, the internal pressure of the high-pressure reactor is observed, and the valves on both sides are used to vent and release the pressure. The pressure in the reactor is controlled to be less than 30MPa. The reaction is kept warm for 1 hour, and the pressure is quickly released to obtain the recycled composite polyester.
[0070] Example 2
[0071] This embodiment provides a method for preparing an impact-resistant and highly thermally conductive recycled PET composite material, comprising the following steps:
[0072] Step 1: Preparation of porous carbon materials
[0073] Weigh: 20.0 g of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 5.4 g of trans, trans-1,3-butadiene-1,4-dicarboxylic acid and 1.0 g of p-toluenesulfonic acid are added into a vacuum reactor, the temperature of the reactor is increased to 260° C., and the reaction is carried out under vacuum insulation for 8 hours to obtain a carbonization promoter precursor;
[0074] Weigh: 8.0mL 40.0wt% peracetic acid solution and 70.0mL dichloromethane are added to the reactor and stirred. The temperature of the reactor is lowered to -5°C, and the mixture is stirred for 8 minutes. 12.0g of carbonization promoter precursor is added to the reactor, and the pH of the system is adjusted to 6 using phosphate buffer, and the mixture is stirred for 2 hours. After the reaction is completed, the reactor is heated to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and the mixture is distilled under reduced pressure until no liquid is extracted to obtain a carbonization promoter;
[0075] Weigh: 16.0 g of recycled polyester and 6.0 g of carbonization promoter are added into a twin-screw extruder, the temperatures of eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260° C., 260° C., 265° C., 265° C., 270° C., 270° C., 280° C., and 280° C., the main engine speed of the twin-screw extruder is 120 rpm, and the pressure is 150 bar, and a green body is obtained by melt extrusion;
[0076] The green body was added into the reactor, and the temperature of the reactor was raised to 80°C at a heating rate of 2°C / min, and kept at that temperature for 1 hour, and then raised to 120°C at a heating rate of 1°C / min, and kept at that temperature for 3 hours, and the material was turned over every 1 hour. After the heating was completed, the green body was naturally cooled to obtain the pre-crystallized green body;
[0077] The pre-crystallized body was transferred to a vacuum drum, the drum temperature was set to 220°C, the vacuum degree was set to 50Pa, the rotation speed was set to 20rpm, and the heat preservation treatment was performed for 3 hours to obtain a hybrid polyester;
[0078] Weigh: 18.0g of hybrid polyester and 10.0g of sawdust, mix and grind, then pass through a 600-mesh sieve to obtain a mixed powder, put the mixed powder into a tubular furnace, pass nitrogen protection, heat the tubular furnace to 80°C at a heating rate of 8°C / min, keep warm for 20min, continue to heat the tubular furnace to 850°C at a heating rate of 2°C / min, after keeping warm for 4h, stop heating, keep nitrogen passing, and let the tubular furnace cool naturally to room temperature to obtain a porous carbon material.
[0079] Step 2: Preparation of cross-linked polyester
[0080] The porous carbon material is ground and passed through a 3000-mesh sieve to obtain a micron carbon filler;
[0081] Weigh: 210.0mL 98.0wt% concentrated sulfuric acid is added to the reactor and stirred. During the stirring process, 4.8g sodium nitrate is added, and after the temperature of the reactor is lowered to 5°C, 36.0g potassium permanganate is added to the reactor. After stirring for 10 minutes, 14.2g of micron carbon filler is added. The temperature of the reactor is raised to 40°C, and the reaction is kept warm for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and 30wt% hydrogen peroxide solution is added dropwise to the reactor until the reaction liquid turns yellow. The reaction liquid is filtered to collect the filter cake, and after washing with deionized water and ethanol for 5 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized carbon filler;
[0082] Weigh: 20.0g of carbon oxide filler, 8.4g of carbonization promoter, 2.0g of triethylamine and 100.0mL of dichloromethane, add them into the reactor and stir, raise the temperature of the reactor to 50°C, keep warm and stir for 2h, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with deionized water and ethanol for 5 times, transfer the filter cake to a drying oven at 60°C and vacuum dry it until the filter cake has a constant weight, to obtain a modified chain extender;
[0083] Weigh: 20.0 g of recycled polyester and 8.0 g of modified chain extender are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260° C., 260° C., 265° C., 265° C., 270° C., 270° C., 280° C., and 280° C., the main engine speed of the twin-screw extruder is 120 rpm, and the pressure is 150 bar to obtain a substrate through melt extrusion;
[0084] The substrate was added into the reactor, and the temperature of the reactor was increased to 80°C at a heating rate of 2°C / min. After being kept warm for 1 hour, the temperature was increased to 120°C at a heating rate of 1°C / min, and kept warm for 3 hours. The material was turned over every 1 hour. After the heating was completed, the substrate was naturally cooled to obtain a pre-crystallized substrate. The pre-crystallized substrate was transferred to a vacuum drum, the drum temperature was set to 220°C, the vacuum degree was set to 40Pa, the rotation speed was 20rpm, and the heat treatment was carried out for 3 hours to obtain a cross-linked polyester.
[0085] Step 3: Preparation of recycled composite polyester
[0086] Weigh: 96.0g of cross-linked polyester, 12.0g of carbon oxide filler, 7.2g of tri(2,4-di-tert-butylphenyl) phosphate, 14.4g of dibutyl phthalate, 4.8g of ethoxylated alkylamine and 5.4g of 2-hydroxy-4-n-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, 280°C, the main engine speed of the twin-screw extruder is 100rpm, the pressure is 120bar, and the recycled composite polyester blank is obtained by melt extrusion;
[0087] The recycled composite polyester blank is placed in a high-pressure reactor, and the high-pressure reactor is placed in a salt bath furnace. After exhausting the air in the high-pressure reactor with carbon dioxide gas, 18MPa carbon dioxide gas is introduced into the high-pressure reactor using a booster device. The temperature of the salt bath furnace is adjusted to 30°C. After insulation treatment for 3 hours, the temperature of the salt bath furnace is raised to 60°C. During the heating process, the internal pressure of the high-pressure reactor is observed, and the valves on both sides are used to vent and release the pressure. The pressure in the reactor is controlled to be less than 30MPa. The reaction is kept warm for 2 hours, and the pressure is quickly released to obtain the recycled composite polyester.
[0088] Example 3
[0089] This embodiment provides a method for preparing an impact-resistant and highly thermally conductive recycled PET composite material, comprising the following steps:
[0090] Step 1: Preparation of porous carbon materials
[0091] Weigh: 20.0 g of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, 5.4 g of trans, trans-1,3-butadiene-1,4-dicarboxylic acid and 1.0 g of p-toluenesulfonic acid are added into a vacuum reactor, the temperature of the reactor is increased to 250° C., and the reaction is carried out under vacuum insulation for 7 hours to obtain a carbonization promoter precursor;
[0092] Weigh: 10.0mL 36.0wt% peracetic acid solution and 72.0mL dichloromethane are added to the reactor and stirred. The temperature of the reactor is lowered to -10°C, and the mixture is stirred for 8 minutes. 21.0g of carbonization promoter precursor is added to the reactor, and the pH of the system is adjusted to 5 using phosphate buffer, and the mixture is stirred for 1.5 hours. After the reaction is completed, the reactor is heated to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and the mixture is distilled under reduced pressure until no liquid is extracted to obtain a carbonization promoter;
[0093] Weigh: 20.0g of recycled polyester and 5.4g of carbonization promoter are added into a twin-screw extruder, the temperatures of eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, 280°C, the main engine speed of the twin-screw extruder is 100rpm, the pressure is 125bar, and a green body is obtained by melt extrusion;
[0094] The green body was added into the reactor, and the temperature of the reactor was raised to 90°C at a heating rate of 2°C / min, and kept at that temperature for 1 hour, and then raised to 120°C at a heating rate of 1°C / min, and kept at that temperature for 3 hours, and the material was turned over every 1 hour. After the heating was completed, the green body was naturally cooled to obtain the pre-crystallized green body;
[0095] The pre-crystallized body was transferred to a vacuum drum, the drum temperature was set to 210°C, the vacuum degree was set to 45Pa, the rotation speed was 18rpm, and the heat preservation treatment was performed for 3 hours to obtain a hybrid polyester;
[0096] Weigh: 18.0g of hybrid polyester and 10.0g of sawdust are mixed and ground, and then passed through a 400-mesh sieve to obtain a mixed powder. The mixed powder is placed in a tubular furnace, and nitrogen is introduced for protection. The tubular furnace is heated to 80°C at a heating rate of 2°C / min, and the temperature is kept warm for 30min. The tubular furnace is further heated to 850°C at a heating rate of 5°C / min. After keeping warm for 3h, the heating is stopped, and nitrogen is kept introduced. The tubular furnace is naturally cooled to room temperature to obtain a porous carbon material.
[0097] Step 2: Preparation of cross-linked polyester
[0098] The porous carbon material is ground and passed through a 2500-mesh sieve to obtain a micron carbon filler;
[0099] Weigh: 204.0mL 98.0wt% concentrated sulfuric acid is added to the reactor and stirred. During the stirring process, 4.2g sodium nitrate is added, and after the temperature of the reactor is lowered to 0°C, 36.0g potassium permanganate is added to the reactor. After being kept warm and stirred for 8min, 12g of micron carbon filler is added, and the temperature of the reactor is raised to 36°C. The reaction is kept warm for 5h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and 30wt% hydrogen peroxide solution is added dropwise to the reactor until the reaction liquid turns yellow. The reaction liquid is filtered to collect the filter cake, and after washing with deionized water and ethanol 4 times, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized carbon filler;
[0100] Weigh: 18.0g of carbon oxide filler, 8.0g of carbonization promoter, 2.0g of triethylamine and 100.0mL of dichloromethane, add them into the reactor and stir, raise the temperature of the reactor to 40°C, keep warm and stir for 1h, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid to collect the filter cake, wash it with deionized water and ethanol 4 times, transfer the filter cake to a drying oven at 60°C and vacuum dry it until the filter cake has a constant weight, to obtain a modified chain extender;
[0101] Weigh: 20.0 g of recycled polyester and 9.6 g of modified chain extender are added to a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260° C., 260° C., 265° C., 265° C., 270° C., 270° C., 280° C., and 280° C., the main engine speed of the twin-screw extruder is 100 rpm, and the pressure is 125 bar to obtain a substrate through melt extrusion;
[0102] The substrate was added into the reactor, and the temperature of the reactor was increased to 90°C at a heating rate of 1°C / min. After keeping the temperature for 1 hour, the temperature was increased to 120°C at a heating rate of 1°C / min, and kept for 3 hours. The material was turned over every 1 hour. After the heating was completed, the substrate was naturally cooled to obtain a pre-crystallized substrate. The pre-crystallized body was transferred to a vacuum drum. The drum temperature was set to 225°C, the vacuum degree was set to 45Pa, the rotation speed was 18rpm, and the heat treatment was performed for 3 hours to obtain a cross-linked polyester.
[0103] Step 3: Preparation of recycled composite polyester
[0104] Weigh: 90.0g of cross-linked polyester, 11.0g of carbon oxide filler, 7.2g of tri(2,4-di-tert-butylphenyl) phosphate, 12.4g of dibutyl phthalate, 4.8g of ethoxylated alkylamine and 5.4g of 2-hydroxy-4-n-octyloxybenzophenone and add them into a twin-screw extruder, the temperatures of the eight temperature sections of the twin-screw extruder from the feed port to the discharge port are 260°C, 260°C, 265°C, 265°C, 270°C, 270°C, 280°C, 280°C, the main engine speed of the twin-screw extruder is 100rpm, the pressure is 125bar, and a recycled composite polyester blank is obtained by melt extrusion;
[0105] The recycled composite polyester blank is placed in a high-pressure reactor, and the high-pressure reactor is placed in a salt bath furnace. After exhausting the air in the high-pressure reactor with carbon dioxide gas, 16MPa carbon dioxide gas is introduced into the high-pressure reactor using a booster device. The temperature of the salt bath furnace is adjusted to 25°C. After insulation treatment for 3 hours, the temperature of the salt bath furnace is raised to 70°C. During the heating process, the internal pressure of the high-pressure reactor is observed, and the valves on both sides are used to vent and release the pressure. The pressure in the reactor is controlled to be less than 30MPa. The reaction is kept warm for 1 hour, and the pressure is quickly released to obtain the recycled composite polyester.
[0106] Comparative Example 1
[0107] The difference between this comparative example and Example 3 is that the step of preparing a carbonization promoter in step 1 is eliminated, and an equal amount of N,N,N',N'-tetracyclyl-4,4'-diaminodiphenylmethane is used in step 1 to replace the carbonization promoter.
[0108] Comparative Example 2
[0109] The difference between this comparative example and Example 3 is that in step 2, multilayer graphene is used in equal amounts to replace the porous carbon material.
[0110] Comparative Example 3
[0111] The difference between this comparative example and Example 3 is that the step of preparing cross-linked polyester in step 2 is eliminated, and in step 3, an equal amount of recycled polyester is used to replace the cross-linked polyester.
[0112] Performance testing:
[0113] The Izod impact strength of the recycled composite polyesters prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1843-2008 "Determination of Izod impact strength of plastics";
[0114] The thermal conductivity of the recycled composite polyester prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 10297-2015 "Hot wire method for determination of thermal conductivity of non-metallic solid materials";
[0115] The volume abrasion loss of the recycled composite polyesters prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)";
[0116] The limiting oxygen index of the recycled composite polyesters prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test";
[0117] The vertical burning rating of the recycled composite polyester prepared in Example 1-3 and Comparative Example 1-3 was tested with reference to the standard GB / T 2408-2021 "Horizontal and vertical methods for determination of combustion performance of plastics";
[0118] The apparent porosity of the porous carbon materials prepared in Examples 1-3, Comparative Example 1 and Comparative Example 3 was tested with reference to the standard GB / T 24529-2009 “Method for Determining the Apparent Porosity of Carbon Materials”. Specific data are shown in Table 1.
[0119] Table 1-Performance test data of each sample
[0120] Data Analysis:
[0121] Comparing and analyzing the data in Table 1 above, the Izod impact strength of the recycled composite polyester prepared by the present invention is 68.2 kJ·m -2 , thermal conductivity reaches 3.828W·(m·K) -1 , Volume wear is only 35mm 3 , the limiting oxygen index is as high as 38.2%, and the vertical combustion grade is V-0, and the apparent porosity of the prepared porous carbon material is 83.5%, "-" means that the corresponding performance test is not performed on this embodiment;
[0122] Explanation analysis:
[0123] The present invention prepares a carbonization promoter to promote the formation of porous carbon materials in the process of carbonization of recycled polyester and sawdust, thereby expanding the utilization options of recycled polyester. The carbonization promoter self-assembles on the surface of an oxidized carbon filler to obtain a modified chain extender. While the modified chain extender hybridizes an organic chain segment, it acts as a nucleation site to promote the recrystallization of a recycled composite polyester blank during recrystallization and micro-foaming, promotes the diffusion of a fluid, and forms a uniform and fine bubble structure. During the combustion process, the carbonization promoter decomposes to form a molten carbon layer, and releases a flame-retardant gas to promote the foaming of the carbon layer, which cooperates with a carbon skeleton to prevent the spread of flames, and finally obtains an impact-resistant, heat-conductive and wear-resistant flame-retardant recycled composite polyester.
[0124] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0125] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an impact-resistant and highly thermally conductive recycled PET composite material, characterized in that: The following steps are involved: S1, adding recycled polyester and a carbonization promoter into a twin-screw extruder for melt extrusion to obtain a green body, and subjecting the green body to solid phase polycondensation to obtain a hybrid polyester; S2, mixing the hybrid polyester and sawdust to obtain a mixed powder after grinding and sieving, carbonizing to obtain a porous carbon material, and modifying the porous carbon material to obtain a modified chain extender; S3, adding the recycled polyester and the modified chain extender into a twin-screw extruder for melt extrusion to obtain a substrate, and repeating the solid phase polycondensation step in step S1 to obtain a cross-linked polyester; S4, melt-blending the cross-linked polyester, the oxidized carbon filler and the auxiliary materials to obtain a recycled composite polyester body; S5. Recrystallize and micro-foam the recycled composite polyester blank with carbon dioxide to obtain the recycled composite polyester.
2. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S1, the ratio of recycled polyester to carbonization promoter is 8-10g:2-3g; the preparation method of the carbonization promoter comprises the following steps: A1. Add N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, trans,trans-1,3-butadiene-1,4-dicarboxylic acid and p-toluenesulfonic acid into a vacuum reactor, increase the temperature of the reactor to 240-260° C., and carry out vacuum insulation reaction for 6-8 hours to obtain a carbonization promoter precursor; A2. Add 30-40wt% peracetic acid solution and dichloromethane into the reactor and stir. Lower the temperature of the reactor to -10-0°C, keep warm and stir for 5-10 minutes, add the carbonizer precursor into the reactor, and use phosphate buffer to adjust the pH of the system to 5-7, keep warm and stir for 0.5-2 hours, and post-treat to obtain the carbonizer.
3. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 2, characterized in that: In step A1, the amount ratio of N-[(10-oxo-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-yl)methyl]-1,3,5-triazine-2,4,6-triamine, trans,trans-1,3-butadiene-1,4-dicarboxylic acid and p-toluenesulfonic acid is 8-10g:2-3g:0.3-0.5g; in step A2, the amount ratio of 30-40wt% peracetic acid solution, dichloromethane and carbonization promoter precursor is 3-5mL:30-40mL:10-12g.
4. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S1, the solid phase polycondensation operation is: B1. Add the green body into a reactor, heat the reactor to 80-90°C at a heating rate of 1-2°C / min, keep the temperature for 1 hour, then heat the reactor to 110-120°C at a heating rate of 1-2°C / min, keep the temperature for 3 hours, turn the material every 1 hour, and naturally cool after heating to obtain a pre-crystallized green body; B2. Transfer the pre-crystallized body to a vacuum drum, set the drum temperature to 200-225°C, the vacuum degree to 40-50Pa, the rotation speed to 15-20rpm, and keep the drum warm for 2-3h to obtain a hybrid polyester.
5. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S2, the dosage ratio of hybrid polyester to sawdust is 1-2g:1g, the mesh size of the sieve is 300-600 mesh, and the carbonization operation is as follows: the mixed powder is placed in a tubular furnace, nitrogen is introduced for protection, the tubular furnace is heated to 70-80°C at a heating rate of 5-8°C / min, and the temperature is kept warm for 20-30min, and the tubular furnace is further heated to 800-850°C at a heating rate of 5-8°C / min. After keeping warm for 2-4h, the heating is stopped, nitrogen is kept introduced, and the tubular furnace is naturally cooled to room temperature to obtain a porous carbon material.
6. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S2, the modification operation of the porous carbon material includes the following steps: C1. Grinding and sieving the porous carbon material to obtain a micron carbon filler; C2, adding 98.0wt% concentrated sulfuric acid to the reactor and stirring, adding sodium nitrate during stirring, and after lowering the temperature of the reactor to 0-5°C, adding potassium permanganate to the reactor, stirring for 5-10 minutes, and then adding micron carbon filler, raising the temperature of the reactor to 35-40°C, and keeping the temperature for reaction for 4-6 hours, and post-treating to obtain oxidized carbon filler; C3. Add carbon oxide filler, carbonization promoter, triethylamine and dichloromethane into a reactor and stir. The temperature of the reactor is raised to 30-50° C. and stirred for 1-2 hours. Post-process to obtain a modified chain extender.
7. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 6, characterized in that: In step C1, the mesh size of the sieve is 2000-3000 mesh; in step C2, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of 98.0wt% concentrated sulfuric acid, sodium nitrate, potassium permanganate and micron carbon filler is 200-210mL:3-5g:30-40g:10-15g; in step C3, the dosage ratio of oxidized carbon filler, carbonization promoter, triethylamine and dichloromethane is 8-10g:3-5g:0.8-1.2g:40-60mL.
8. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S3, the amount ratio of recycled polyester and modified chain extender is 8-10g:3-5g; in step S4, the auxiliary materials include: antioxidant, plasticizer, antistatic agent and stabilizer, and the amount ratio of cross-linked polyester, oxidized carbon filler, antioxidant, plasticizer, antistatic agent and stabilizer is 80-100g:10-12g:6-8g:10-15g:3-5g:4-6g.
9. The method for preparing a shock-resistant and highly thermally conductive recycled PET composite material according to claim 1, characterized in that: In step S5, the carbon dioxide recrystallization and micro-foaming operations are as follows: placing the regenerated composite polyester blank in a high-pressure reactor, placing the high-pressure reactor in a salt bath furnace, using carbon dioxide gas to exhaust the air in the high-pressure reactor, using a booster device to pass 15-18MPa carbon dioxide gas into the high-pressure reactor, adjusting the temperature of the salt bath furnace to 25-30°C, and after heat preservation for 2-4h, the temperature of the salt bath furnace is raised to 60-80°C. During the heating process, the internal pressure of the high-pressure reactor is observed, and the valves on both sides are used to vent and release the pressure, and the pressure in the reactor is controlled to be less than 30MPa. The heat preservation reaction is carried out for 1-2h, and the pressure is quickly released to obtain the regenerated composite polyester.
10. An impact-resistant and highly thermally conductive recycled PET composite material, characterized in that: The impact-resistant and highly thermally conductive recycled PET composite material is obtained by processing using the preparation method of the impact-resistant and highly thermally conductive recycled PET composite material described in any one of claims 1 to 9.
Citation Information
Patent Citations
Water-resistant flame-retardant epoxy resin curing agent and preparation method thereof
CN113045733A
Flame-retardant enhanced regenerated PET composite material
CN113999499A
Environment-friendly regenerated PET modified PC / ABS alloy and preparation method thereof
CN115895225A
Halogen-free flame-retardant PPO composite material and preparation method thereof
CN117362979A
Fireproof powder coating with antistatic effect and preparation method thereof
CN118185433A